Abraham Lincoln's world, 1809-1865 - Foster, Genevieve, 1893- (New York, Scribner, 1944)
A historical survey of Europe, Asia, Africa, and the Americas during the lifetime of Abraham Lincoln, examining people, places, and events which gave color to the world of the nineteenth century.
3 10 13 33 35 39
Keywords: Lincoln, Abraham, -- 1809-1865 -- Juvenile literature; Lincoln, Abraham, -- 1809-1865.; History, Modern -- 19th century